Crystal and molecular structure of (2Z, 5Z)-3-(2-methoxyphenyl)-2-[(2-methoxyphenyl) imino]-5-(4-nitrobenzylidene) thiazolidin-4-one - Chouaih, Abdelkader; Djafri, Ahmed; Daran, J-C; Hamzaoui, Fodil (Acta Crystallographica Section E: Crystallographic Communications, 2017)
In the title compound, C24H19N3O5S, the thiazole ring (r.m.s. deviation = 0.012 Å) displays a planar geometry and is surrounded by three fragments, two methoxyphenyl and one nitrophenyl. The thiazole ring is almost in the same plane as the nitrophenyl ring, making a dihedral angle of 20.92 (6)°. The two methoxyphenyl groups are perpendicular to the thiazole ring [dihedral angles of 79.29 (6) and 71.31 (7)° and make a dihedral angle of 68.59 (7)°. The molecule exists in an Z,Z conformation with respect to the C=N imine bond. In the crystal, a series of C—H⋯N, C—H⋯O and C—H⋯S hydrogen bonds, augmented by several π–π(ring) interactions, produce a three-dimensional architecture of molecules stacked along the b-axis direction. The experimentally derived structure is compered with that calculated theoretically using DFT(B3YLP) methods.
Keywords: crystal structure; thiazolidin-4-one; DFT calculations; hydrogen bonding; – interactions